Emerging manufacturers engagements in the COVID −19 vaccine research, development and supply. Issue 34 (22nd July 2020) - Pagliusi, Sonia; Jarrett, Stephen; Hayman, Benoit; Kreysa, Ulrike; Prasad, Sai D.; Reers, Martin; Hong Thai, Pham; Wu, Ke; Zhang, Youn Tao; Baek, Yeong Ok; Kumar, Anand; Evtushenko, Anatoly; et al.
Highlights: Broad research and development is key to achieving an effective safe COVID-19 vaccine. Currently 19 Network members engaged in research & development of 22 COVID-19 vaccines. Collectively 37 Network manufacturers supply around 3.5 billion vaccine doses annually. Existing manufacturing capabilities can accelerate the availability of COVID vaccines. Deploying available vaccine production capacity, will save time, resources and lives. Abstract: The World Health Organization declared the COVID-19 disease as a pandemic requiring a rapid response. Through online search, direct communication with network members and an internal survey, engagements of developing countries' vaccine manufacturers' network members in the research and development of COVID-19 vaccines and their capacities in the manufacturing, fill-finish and distribution of vaccines were assessed. Currently, 19 network members engaged in research and development of COVID-19 vaccines, using six principal technology platforms. In addition, an internal survey showed that the number of vaccines supplied collectively by 37 members, in 2018–19, was about 3.5 billion doses annually. Almost a third of network members having vaccines prequalified by the World Health Organization comply with international regulations and mechanisms to distribute vaccines across borders. The use of existing manufacturing, fill-finish and distribution capabilities can support an efficient roll-out of vaccines against COVID-19, while maintaining supply security of existing vaccines for on-going immunization programmes.